2011
DOI: 10.1111/j.1464-410x.2011.10480.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of transperineal template prostate biopsies in restaging men with prostate cancer managed by active surveillance

Abstract: What ' s known on the subject? and What does the study add? The optimal method of active surveillance in prostate cancer remains unknown. This study is one of the fi rst to report on the role of transperineal template prostate biopsies in active surveillance. It demonstrates that around one third of men are reclassifi ed with more signifi cant prostate cancer at an early stage in their management. This is a higher proportion than reported in contemporary cancers using standard transrectal biopsies for restagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 43 publications
3
66
0
3
Order By: Relevance
“…About half of the patients' tumors were localized in the anterior lob. [17,18] MR image assisted transperineal biopsy is not superior to ultrasound assisted biopsy in patients whose tumors are low grade and volume similar to AS patients. [19] But MR image assisted and 3D mapping method has shown that 25% of AS patients have GS ≥7 tumor and 61% of them are bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…About half of the patients' tumors were localized in the anterior lob. [17,18] MR image assisted transperineal biopsy is not superior to ultrasound assisted biopsy in patients whose tumors are low grade and volume similar to AS patients. [19] But MR image assisted and 3D mapping method has shown that 25% of AS patients have GS ≥7 tumor and 61% of them are bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…TPSB is reported to more accurately detect and characterise the extent and grade of PCa [16,19]. We, therefore, decided to offer this as an option to those considering AS after conventional TRUS biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…yaptıkları çalışmada 301 hastanın biyopsi ve RP sonuçlarını karşılaştırmış ve GS artış oranı 18 ve üzeri kor biyopsi alınan olgularda %23.5, 10-12 kor biyopsi alınanlarda ise %47.9 olarak rapor edilmiştir (39). Transrektal yöntem ile Aİ'e dahil edilme kriterlerine uygun bulunan 101 olgunun, transperineal yolla yapılan tekrar evrelendirilmesinde olguların %34'de anlam Pca olduğu, diğer bir ifade ile transrektal yolun bazı hastalarda düşük evrelemeye eden olduğu gösterilmiştir (40).…”
Section: Biyopsisi Gs=6 Olan Bir Olgunun Rp Gs'u Benign Idi (Toplam;unclassified